ES fiber containing wormwood active ingredient and its application in sweat-absorbing patch

By using ES fiber containing mugwort active ingredients in sweat-absorbent patches, the problems of insufficient hygroscopic properties and easy breeding of bacteria are solved, and the effective hygroscopic and antibacterial effects are achieved.

CN118007274BActive Publication Date: 2025-02-28SISLAN (NANYANG) PHARM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410111317.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2025-02-28
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

Traditional sweat-absorbing patches have problems such as insufficient hygroscopic performance and easy breeding of bacteria during use, which is difficult to meet people's needs for antibacterial and hygroscopic performance.

Method used

Develop an ES fiber containing mugwort active ingredients to improve the hygroscopic, antibacterial and mechanical properties of the fibers by adding specific materials such as high-density polyethylene, carbon nanotubes, modified coconut shell activated carbon and mugwort extract to the core and cortex.

Benefits of technology

The application of this fiber in sweat-absorbing patches can effectively inhibit bacterial growth and odor generation, have excellent hygroscopic and antibacterial properties, and improve the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004683464060000131
    Figure BDA0004683464060000131
  • Figure BDA0004683464060000132
    Figure BDA0004683464060000132
  • Figure BDA0004683464060000181
    Figure BDA0004683464060000181
Patent Text Reader

Abstract

The present invention provides an ES fiber containing wormwood active ingredients and its application in sweat-absorbing patch, including a core layer and a cortex with a weight ratio of 10: (8.8-9.4); the core layer is composed of the following weight parts of materials: 91-94 parts of polypropylene, 15-18 parts of high-density polyethylene, 8-10 parts of super absorbent resin, 2-3 parts of nano-silicon dioxide, 3-5 parts of carbon nanotubes, 6-8 parts of wormwood extract, and 2-5 parts of processing aids; the cortex is composed of the following weight parts of materials: 84-88 parts of polyethylene, 15-20 parts of super absorbent resin, 3-5 parts of nano-silicon dioxide, 2-4 parts of modified coconut shell activated carbon, 5-7 parts of wormwood extract, and 2-4 parts of processing aids. The ES fiber prepared by the present invention can effectively inhibit bacterial growth and odor generation, has excellent moisture absorption and antibacterial properties, and can be applied to the production of sweat-absorbing patches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber manufacturing, and in particular to ES fiber containing wormwood active ingredients and application thereof in a sweat-absorbing patch. Background Art

[0002] ES fiber is a polyolefin fiber developed by Chisso Corporation of Japan. As a two-component core-skin composite fiber, the cortex has a low melting point and good softness, while the core has a high melting point and high strength. After heat treatment, part of the cortex melts and acts as a bond, while the rest remains in a fiber state and has the characteristic of low thermal shrinkage. This fiber is particularly suitable for the production of sanitary materials, thermal insulation filling materials, filter materials and other products using hot air penetration technology.

[0003] In recent years, people's awareness of health and environmental protection has gradually increased, and more and more people have begun to pay attention to the natural, environmentally friendly and healthy attributes of products. As a natural herb, wormwood has multiple biological activities such as antibacterial, anti-inflammatory, and mosquito repellent, and is widely used in medical, health care, beauty and other fields.

[0004] Patent CN111118656B provides an ES fiber containing wormwood extract and a preparation method thereof. The ES fiber contains wormwood extract of 0.1-5%. The preparation method includes the preparation of a functional modifier containing wormwood extract, the preparation of a cortical material, the preparation of a core material, composite spinning and post-treatment. The ES fiber containing wormwood extract prepared by the method has a natural antibacterial effect, with an antibacterial rate of 96.5-99.2% for Escherichia coli, 95.0-97.2% for Staphylococcus aureus, and 94.5-96.0% for Candida albicans. At the same time, the fiber density of the ES fiber is 0.98-1.20 g / cm 3 , fineness 1.2-1.6dtex, breaking strength 6.2cN / dtex-6.6cN / dtex, breaking elongation 4.5-6.0%. This new type of composite fiber has excellent comprehensive performance.

[0005] As people's living standards improve, the demand for personal hygiene and health is growing. As a personal hygiene product, sweat-absorbing patches play an important role in meeting people's daily needs. However, traditional sweat-absorbing patches often have some problems during use, such as insufficient moisture absorption and easy breeding of bacteria. In order to solve these problems, it is particularly important to develop a new type of sweat-absorbing patch with both antibacterial and moisture absorption properties. Based on this, the present invention provides an ES fiber containing wormwood active ingredients and its application in sweat-absorbing patches. Summary of the invention

[0006] The purpose of the present invention is to provide an ES fiber containing wormwood active ingredients and its application in a sweat-absorbing patch. The ES fiber in the present invention can be made into a sweat-absorbing patch, which effectively inhibits bacterial growth and odor generation, has excellent moisture absorption and antibacterial properties, and improves the user experience of the sweat-absorbing patch.

[0007] In one aspect, the present invention provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:(8.8-9.4);

[0008] The core layer is composed of the following materials in parts by weight: 91-94 parts of polypropylene, 15-18 parts of high-density polyethylene, 8-10 parts of highly absorbent resin, 2-3 parts of nano-silicon dioxide, 3-5 parts of carbon nanotubes, 6-8 parts of wormwood extract, and 2-5 parts of processing aids;

[0009] The skin layer is composed of the following materials in parts by weight: 84-88 parts of polyethylene, 15-20 parts of highly absorbent resin, 3-5 parts of nano silicon dioxide, 2-4 parts of modified coconut shell activated carbon, 5-7 parts of wormwood extract, and 2-4 parts of processing aid.

[0010] Furthermore, the high-density polyethylene has a weight average molecular weight of 3-6 million, and a melt index of 5-15 g / 10 min at 190° C. and 2.16 kg.

[0011] Furthermore, the super absorbent resin is prepared from the following raw materials:

[0012] Mixed monomers: weight ratio of (18-20):(9-10):(12-13) acrylic acid, acrylamide, sodium allyl sulfonate;

[0013] 6-8% by weight of pretreated montmorillonite relative to the weight of the mixed monomers;

[0014] 0.1-0.15% initiator relative to the weight of the mixed monomers;

[0015] 0.12-0.14% crosslinking agent relative to the weight of the mixed monomers.

[0016] Furthermore, the pretreatment step is: pretreatment of the montmorillonite by high temperature baking at 320-340°C for 2-3h.

[0017] Furthermore, the preparation method of the highly absorbent resin comprises: neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution of 65-70%, adding acrylamide and sodium allyl sulfonate and stirring until all dissolved to obtain a monomer mixed solution, adding pretreated montmorillonite, an initiator and a cross-linking agent at a temperature of 30-34° C. and stirring for 30-40 minutes, then heating to 64-68° C. and reacting at a constant temperature for 4-5 hours, cooling to room temperature after the reaction is completed, and washing and drying the product.

[0018] Furthermore, the washing liquid is ethanol, and the drying temperature is 80-90°C.

[0019] Furthermore, the preparation method of the modified coconut shell activated carbon includes: mixing coconut shell activated carbon with deionized water at a ratio of 1g / (4-5)mL and heating and boiling for 30-40min, rinsing with deionized water after cooling, filtering, drying and grinding the coconut shell activated carbon at 60-70°C for later use; weighing 20-22g of the treated coconut shell activated carbon, adding 200mL of 1mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 24-26°C for 10-12h, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 100-105°C.

[0020] Furthermore, the processing aid includes an antioxidant, a dispersant and a coupling agent in a weight ratio of (5-6): (2-3): (4-6).

[0021] Furthermore, the antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1-1.2).

[0022] Furthermore, the dispersant is styrene-maleic anhydride copolymer and / or polyethylene wax.

[0023] Furthermore, the weight ratio of the styrene-maleic anhydride copolymer to the polyethylene wax is 1:

[0024] (1.1-1.2).

[0025] Furthermore, the coupling agent includes a silane coupling agent and a titanate coupling agent.

[0026] Furthermore, the silane coupling agent includes methyltrichlorosilane coupling agent and / or vinylsilane coupling agent; the titanate coupling agent includes isopropyl titanate triisostearate.

[0027] On the other hand, the present invention also provides a method for preparing ES fiber containing mugwort active ingredients, the steps comprising: (1) adding a core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding a skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0028] The ES fiber containing the active ingredient of mugwort prepared in the present invention is applied to a sweat-absorbing patch.

[0029] The beneficial effects of the present invention are:

[0030] (1) In the present invention, the ES fiber core layer and the skin layer are configured with different raw materials and components, added into a twin-screw extruder to obtain a melt, and the ES fiber is blended and spun to form the ES fiber. The selection of raw materials can effectively improve the moisture absorption performance of the fiber, can quickly absorb sweat, and keep the skin dry and comfortable;

[0031] (2) In the present invention, high-density polyethylene and carbon nanotubes are added as raw materials to the core layer raw materials, and the two are blended to achieve carbon nanotube modification of high-density polyethylene, which effectively improves the mechanical properties of ES fibers; at the same time, the interaction between the two also effectively fixes the wormwood extract, which also effectively maintains the antibacterial properties of the ES fibers after washing;

[0032] (3) In the present invention, the moisture absorption property of ES fiber is improved by using a water-absorbent resin, and montmorillonite and its pretreatment method are selected to improve the mechanical properties and antibacterial properties of the fiber;

[0033] (4) The present invention screens modified coconut shell activated carbon and carbon nanotubes, controls the interaction between the two, and improves the performance of ES fiber. In addition, carbon nanotubes are selected in the core layer material, and modified coconut shell activated carbon is selected in the skin layer material to more effectively play their respective roles, so as to achieve the optimization of ES fiber performance.

[0034] (5) The ES fiber of the present invention contains wormwood extract, which has natural antibacterial, anti-inflammatory and deodorizing functions and is harmless to the human body. The ES fiber containing wormwood active ingredients of the present invention and its application in sweat-absorbing patches provide people with a new type of personal hygiene product with broad market prospects and commercial value.

[0035] (6) The ES fiber containing the active ingredient of wormwood of the present invention is widely used in sweat-absorbing patches, and can be made into sweat-absorbing patches of various shapes and sizes, such as round, square, strip, etc. When in use, the sweat-absorbing patch is pasted on the parts that need to absorb moisture, such as the armpit, forehead, neck, back, etc., which can effectively absorb sweat and keep the skin dry and comfortable. At the same time, due to the addition of wormwood extract, carbon nanotubes and activated carbon, the sweat-absorbing patch also has the functions of antibacterial, anti-inflammatory, deodorization, etc., which improves the safety of use. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The raw materials in the present invention: coconut shell activated carbon was purchased from Chengde Jibei Yanshan Activated Carbon Co., Ltd., and wormwood extract was purchased from Xi'an Tianbao Biotechnology Co., Ltd. In the following examples, the initiator for preparing the super absorbent resin was ammonium persulfate, and the crosslinking agent was N,N'-methylenebisacrylamide.

[0038] Example 1

[0039] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0040] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0041] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0042] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0043] Wherein, the super absorbent resin is prepared from the following raw materials:

[0044] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0045] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0046] 0.12% initiator relative to the weight of the mixed monomers;

[0047] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0048] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0049] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0050] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0051] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0052] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0053] Example 2

[0054] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:(8.8-9.4);

[0055] The core layer is composed of the following materials in parts by weight: 91 parts of polypropylene, 17 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 6 parts of wormwood extract, and 3 parts of processing aids;

[0056] The skin layer is composed of the following materials in parts by weight: 85 parts of polyethylene, 18 parts of super absorbent resin, 4 parts of nano silicon dioxide, 4 parts of modified coconut shell activated carbon, 5 parts of wormwood extract, and 4 parts of processing aid;

[0057] The high-density polyethylene has a weight average molecular weight of 6 million and a melt index of 12 g / 10 min at 190° C. and 2.16 kg.

[0058] Wherein, the super absorbent resin is prepared from the following raw materials:

[0059] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (18):(10):(13);

[0060] 8% by weight of pretreated montmorillonite relative to the weight of the mixed monomers;

[0061] 0.15% initiator relative to the weight of the mixed monomers;

[0062] 0.14% cross-linking agent relative to the weight of the mixed monomers;

[0063] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 340°C for 3h to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% and a neutralization degree of 70% to obtain a neutralized acrylic acid solution, adding acrylamide and sodium allyl sulfonate and stirring until all are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 34°C and stirring for 40min, then heating to 68°C and reacting at a constant temperature for 5h, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 90°C to obtain the obtained product.

[0064] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (5) mL, heating and boiling for 40 min, cooling, rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 70° C. for later use; weighing 22 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 26° C. for 12 h, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 100-105° C. to obtain the modified coconut shell activated carbon;

[0065] The processing aid comprises an antioxidant, a dispersant and a coupling agent in a weight ratio of (6): (3): (4);

[0066] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0067] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0068] Example 3

[0069] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:(8.8-9.4);

[0070] The core layer is composed of the following materials in parts by weight: 93 parts of polypropylene, 16 parts of high-density polyethylene, 8 parts of highly absorbent resin, 2 parts of nano-silicon dioxide, 3 parts of carbon nanotubes, 6 parts of wormwood extract, and 2 parts of processing aids;

[0071] The skin layer is composed of the following materials in parts by weight: 84 parts of polyethylene, 15 parts of super absorbent resin, 3 parts of nano-silicon dioxide, 2 parts of modified coconut shell activated carbon, 5 parts of wormwood extract, and 2 parts of processing aid;

[0072] The high-density polyethylene has a weight average molecular weight of 6 million and a melt index of 8 g / 10 min at 190° C. and 2.16 kg.

[0073] Wherein, the super absorbent resin is prepared from the following raw materials:

[0074] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (18):(9):(13);

[0075] 6% of pre-treated montmorillonite relative to the weight of the mixed monomers;

[0076] 0.1% initiator relative to the weight of the mixed monomers;

[0077] 0.12% cross-linking agent relative to the weight of the mixed monomers;

[0078] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 320°C for 2h to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 65%, adding acrylamide and sodium allyl sulfonate and stirring until all dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 30°C and stirring for 30min, then heating to 64°C and reacting at a constant temperature for 4h, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 80°C to obtain the obtained product.

[0079] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4) mL, heating and boiling for 30 min, cooling, rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 60°C for later use; weighing 20 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 24-26°C for 10 h, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 100°C;

[0080] The processing aid comprises an antioxidant, a dispersant and a coupling agent in a weight ratio of (5): (2): (4);

[0081] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0082] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0083] Example 4

[0084] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:(8.8-9.4);

[0085] The core layer is composed of the following materials in parts by weight: 94 parts of polypropylene, 15 parts of high-density polyethylene, 10 parts of highly absorbent resin, 2 parts of nano-silicon dioxide, 5 parts of carbon nanotubes, 6 parts of wormwood extract, and 2 parts of processing aids;

[0086] The skin layer is composed of the following materials in parts by weight: 88 parts of polyethylene, 15 parts of super absorbent resin, 5 parts of nano-silicon dioxide, 2 parts of modified coconut shell activated carbon, 7 parts of wormwood extract, and 2 parts of processing aid;

[0087] The high-density polyethylene has a weight average molecular weight of 4 million and a melt index of 5-15 g / 10 min at 190° C. and 2.16 kg.

[0088] Wherein, the super absorbent resin is prepared from the following raw materials:

[0089] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (18):(10):(12);

[0090] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0091] 0.1% initiator relative to the weight of the mixed monomers;

[0092] 0.14% cross-linking agent relative to the weight of the mixed monomers;

[0093] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 340°C for 2h to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% and a neutralization degree of 70% to obtain a neutralized acrylic acid solution, adding acrylamide and sodium allyl sulfonate and stirring until all are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 34°C and stirring for 30min, then heating to 68°C and reacting at a constant temperature for 4h, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 83°C to obtain the obtained product.

[0094] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4) mL, heating and boiling for 30 min, cooling, rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 70° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 h, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 103° C. to obtain the modified coconut shell activated carbon;

[0095] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (6): (2): (4);

[0096] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0097] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0098] Test Example 1: The performance of the ES fibers prepared in the above-mentioned Examples 1-4 was investigated, and the prepared ES fibers were subjected to the following tests:

[0099] Mechanical properties test: Test the breaking strength and breaking elongation of each ES fiber according to GB / T 14344-2008;

[0100] Single yarn fineness: tested according to GB / T 14344-2008;

[0101] Hygroscopic constant: ES fiber is made into fiber non-woven fabric (weight 400g / m 2 ) Fabric, tested according to JISL1079;

[0102] Antibacterial performance test: According to the method in GB / T20944.3-2008, the inhibition rate of each ES fiber against Staphylococcus aureus, Escherichia coli, and Candida albicans was tested, and the inhibition rate against Staphylococcus aureus, Escherichia coli, and Candida albicans was tested after washing 100 times.

[0103] The test results are shown in Tables 1 and 2 below:

[0104] Table 1

[0105]

[0106] Table 2

[0107]

[0108] The ES fiber containing the active ingredient of mugwort prepared in the above-mentioned embodiment has a moisture absorption constant of 0.53-0.55, which is a high value, and its water absorption rate is also high. It can effectively absorb moisture while achieving antibacterial properties, and has excellent mechanical properties and good durability, and can be used in the production of sweat-absorbing patches.

[0109] In order to explore the effect of the interaction between high-density polyethylene and carbon nanotubes on the performance of ES fibers, comparative examples 1-2 are set as follows in the present invention:

[0110] Comparative Example 1

[0111] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0112] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 7 parts of wormwood extract, and 3 parts of processing aids;

[0113] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0114] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0115] Wherein, the super absorbent resin is prepared from the following raw materials:

[0116] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0117] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0118] 0.12% initiator relative to the weight of the mixed monomers;

[0119] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0120] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0121] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0122] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0123] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0124] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0125] Comparative Example 2

[0126] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0127] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 9 parts of super absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aid;

[0128] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0129] Wherein, the super absorbent resin is prepared from the following raw materials:

[0130] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0131] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0132] 0.12% initiator relative to the weight of the mixed monomers;

[0133] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0134] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0135] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0136] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0137] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0138] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0139] Comparative Example 3

[0140] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0141] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0142] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0143] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 5 g / 10 min at 190° C. and 2.16 kg.

[0144] Wherein, the super absorbent resin is prepared from the following raw materials:

[0145] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0146] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0147] 0.12% initiator relative to the weight of the mixed monomers;

[0148] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0149] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0150] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0151] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0152] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0153] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0154] Test Example 2: The performance of the ES fibers prepared in the above-mentioned Comparative Examples 1-3 was investigated, and the test results are shown in Tables 3 and 4 below:

[0155] Table 3

[0156]

[0157] Table 4

[0158]

[0159]

[0160] In order to explore the effect of water-absorbent resin on the performance of ES fiber, comparative examples 4-5 are set as follows in the present invention:

[0161] Comparative Example 4

[0162] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0163] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0164] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0165] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0166] Wherein, the super absorbent resin is prepared from the following raw materials:

[0167] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0168] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0169] 0.12% initiator relative to the weight of the mixed monomers;

[0170] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0171] The preparation method of the highly absorbent resin comprises: neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the highly absorbent resin.

[0172] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0173] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0174] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0175] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0176] Comparative Example 5

[0177] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0178] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0179] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of modified coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0180] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0181] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0182] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0183] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0184] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0185] Test Example 3: The performance of the ES fibers prepared in the above-mentioned Comparative Examples 4-5 was investigated, and the test results are shown in Tables 5 and 6 below:

[0186] Table 5

[0187]

[0188] Table 6

[0189]

[0190] In order to explore the effect of the interaction between modified coconut shell activated carbon and carbon nanotubes on the performance of ES fibers, comparative examples 6-8 are set as follows in the present invention:

[0191] Comparative Example 6

[0192] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0193] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0194] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano silicon dioxide, 3 parts of coconut shell activated carbon, 6 parts of wormwood extract, and 3 parts of processing aid;

[0195] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0196] Wherein, the super absorbent resin is prepared from the following raw materials:

[0197] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0198] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0199] 0.12% initiator relative to the weight of the mixed monomers;

[0200] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0201] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0202] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0203] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0204] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0205] Comparative Example 7

[0206] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0207] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of carbon nanotubes, 7 parts of wormwood extract, and 3 parts of processing aids;

[0208] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano silicon dioxide, 6 parts of wormwood extract, and 3 parts of processing aid;

[0209] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0210] Wherein, the super absorbent resin is prepared from the following raw materials:

[0211] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0212] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0213] 0.12% initiator relative to the weight of the mixed monomers;

[0214] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0215] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0216] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0217] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0218] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0219] Comparative Example 8

[0220] This embodiment provides an ES fiber containing an active ingredient of mugwort, comprising a core layer and a skin layer in a weight ratio of 10:9.1;

[0221] The core layer is composed of the following materials in parts by weight: 92 parts of polypropylene, 16 parts of high-density polyethylene, 9 parts of highly absorbent resin, 2.5 parts of nano-silicon dioxide, 4 parts of modified coconut shell activated carbon, 7 parts of wormwood extract, and 3 parts of processing aids;

[0222] The skin layer is composed of the following materials in parts by weight: 86 parts of polyethylene, 17 parts of super absorbent resin, 4 parts of nano-silicon dioxide, 3 parts of carbon nanotubes, 6 parts of wormwood extract, and 3 parts of processing aid;

[0223] The high-density polyethylene has a weight average molecular weight of 5 million and a melt index of 10 g / 10 min at 190° C. and 2.16 kg.

[0224] Wherein, the super absorbent resin is prepared from the following raw materials:

[0225] Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (19):(9.5):(12.5);

[0226] 7% by weight of pretreated montmorillonite relative to the mixed monomers;

[0227] 0.12% initiator relative to the weight of the mixed monomers;

[0228] 0.13% cross-linking agent relative to the weight of the mixed monomers;

[0229] The preparation method of the highly absorbent resin comprises: pre-treating montmorillonite by high-temperature baking at 330° C. for 2.5 hours to obtain pre-treated montmorillonite; neutralizing an acrylic acid aqueous solution with a sodium hydroxide aqueous solution with a mass concentration of 30% to obtain a neutralized acrylic acid solution with a neutralization degree of 67%, adding acrylamide and sodium allyl sulfonate and stirring until all of them are dissolved to obtain a monomer mixed solution, adding the pre-treated montmorillonite, an initiator and a cross-linking agent at a temperature of 32° C. and stirring for 35 minutes, then heating to 66° C. and reacting at a constant temperature for 4.5 hours, cooling to room temperature after the reaction is completed, washing the product with ethanol, and drying at 85° C. to obtain the obtained product.

[0230] The preparation method of the modified coconut shell activated carbon comprises: mixing coconut shell activated carbon with deionized water at a ratio of 1 g / (4.5) mL, heating and boiling for 35 minutes, cooling and then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon at 65° C. for later use; weighing 21 g of the treated coconut shell activated carbon, adding 200 mL of 1 mol / L sodium hydroxide solution, oscillating in a water bath oscillator at a temperature of 25° C. for 11 hours, rinsing with deionized water until the pH value is neutral, and drying at a temperature of 102° C. to obtain the modified coconut shell activated carbon;

[0231] The processing aid includes an antioxidant, a dispersant, and a coupling agent in a weight ratio of (5.5):(2.5):(5);

[0232] The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1.1); the dispersant is styrene-maleic anhydride copolymer and polyethylene wax; the weight ratio of the styrene-maleic anhydride copolymer and polyethylene wax is 1:(1.15); the coupling agent includes a silane coupling agent and a titanate coupling agent in a 1:1 ratio; the silane coupling agent includes a methyltrichlorosilane coupling agent and a vinyl silane coupling agent in a 1:2 ratio; the titanate coupling agent includes isopropyl triisostearate titanate.

[0233] The preparation method of ES fiber containing mugwort active ingredients in this embodiment comprises the following steps: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) passing the core layer melt and the skin layer melt into a composite spinning machine via a metering pump to perform melt spinning to obtain ES fiber.

[0234] Test Example 4: The performance of the ES fibers prepared in the above-mentioned Comparative Examples 6-8 was investigated, and the test results are shown in Tables 7 and 8 below:

[0235] Table 7

[0236]

[0237] Table 8

[0238]

[0239] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. An ES fiber containing an active ingredient of Artemisia argyi, characterized in that: It includes a core layer and a skin layer in a weight ratio of 10:(8.8-9.4); The core layer is composed of the following materials in parts by weight: 91-94 parts of polypropylene, 15-18 parts of high-density polyethylene, 8-10 parts of highly absorbent resin, 2-3 parts of nano-silicon dioxide, 3-5 parts of carbon nanotubes, 6-8 parts of wormwood extract, and 2-5 parts of processing aids; The cortex is composed of the following materials in parts by weight: 84-88 parts of polyethylene, 15-20 parts of super absorbent resin, 3-5 parts of nano silicon dioxide, 2-4 parts of modified coconut shell activated carbon, 5-7 parts of wormwood extract, and 2-4 parts of processing aids; The highly water-absorbent resin is prepared from the following raw materials: Mixed monomers: acrylic acid, acrylamide, sodium allyl sulfonate in a weight ratio of (18-20): (9-10): (12-13); 6-8% of pretreated montmorillonite relative to the weight of the mixed monomers; The pretreatment step is: pretreatment of the montmorillonite by high temperature baking at 320-340°C for 2-3h; 0.1-0.15% initiator relative to the weight of the mixed monomers; 0.12-0.14% cross-linking agent relative to the weight of the mixed monomers; The preparation method of the modified coconut shell activated carbon comprises: adding coconut shell activated carbon to deionized water, mixing, heating and boiling, cooling, then rinsing with deionized water, filtering, drying and grinding the coconut shell activated carbon for later use; weighing the treated coconut shell activated carbon, adding it to an alkaline solution, oscillating in a water bath oscillator, then rinsing with deionized water until the pH value is neutral, and drying; the high-density polyethylene has a weight-average molecular weight of 3-6 million, and a melt index of 8-15 g / 10 min at 190° C. and 2.16 kg.

2. The ES fiber containing wormwood active ingredients according to claim 1, characterized in that: The processing aid comprises an antioxidant, a dispersant and a coupling agent in a weight ratio of (5-6): (2-3): (4-6).

3. The ES fiber containing wormwood active ingredients according to claim 2, characterized in that: The antioxidants are antioxidant 330 and antioxidant 1010 in a weight ratio of 1:(1-1.2); the dispersant is styrene-maleic anhydride copolymer and / or polyethylene wax.

4. The ES fiber containing wormwood active ingredients according to claim 2, characterized in that: The coupling agent includes a silane coupling agent and a titanate coupling agent.

5. A method for preparing ES fiber containing wormwood active ingredients as claimed in any one of claims 1 to 4, characterized in that the steps include: (1) adding the core layer raw material into a twin-screw extruder to obtain a core layer melt; (2) adding the skin layer raw material into a twin-screw extruder to obtain a skin layer melt; (3) The core layer melt and the skin layer melt are fed into a composite spinning machine through a metering pump for melt spinning to obtain ES fibers.

6. An ES fiber containing wormwood active ingredients as described in any one of claims 1 to 4, applied to a sweat-absorbing patch.

Citation Information

Patent Citations

  • An ES fiber containing Artemisia argyi extract and its preparation method

    CN111118656B

  • Antibacterial composite short fiber and preparation method thereof

    CN110565203A

  • ES large biological fiber containing wormwood active ingredients

    CN112553709A

  • Production method of ES composite short fibers with adsorption function

    CN116949597A